Behavior of Viscous Liquid Byproduct Formed in Exhaust Tube by Silicon Carbide Epitaxial Growth. (1st January 2019) - Mizushima, Ichiro; Habuka, Hitoshi
Abstract : The behavior of the by-product produced in an exhaust tube by the semiconductor silicon carbide epitaxial growth process was evaluated. The by-product layer was a dark-colored viscous liquid; it captured precursor gases and gaseous by-products, such as hydrogen, monosilane, propane, hydrogen chloride and chlorosilanes. These captured gases were spontaneously emitted in ambient nitrogen at room temperature. By an etching process using a chlorine trifluoride gas at low concentrations in ambient nitrogen, the by-product layer could be safely decomposed to gaseous fluorides of silicon and carbon. After finishing the etching, there remained a small amount of residue which included particles of carbon, silicon carbide and related compounds. Based on these results, the by-product layer formation process was discussed.